Enzyme-linked immunosorbent assay to measure serum ferritin in toucans (Ramphastidae sp.) - Meindel, Mandy J. (Kansas State University, 2015)
Background: Iron storage disease has proven to be a serious health concern for captive toucans. Physiologic mechanisms to efficiently extract iron from naturally iron-deficient diets appear the likely cause of iron overload when fed iron-sufficient diets in captivity. Iron overload can result in diabetes, heart failure, and even death. Serum ferritin concentrations are considered the most reliable screening tool to predict total body iron stores in many species, but an assay has not been available to measure serum ferritin in toucans. Objective: The purpose of this study was to develop an enzyme-linked immunosorbent assay (ELISA) to measure serum ferritin in toucans using a polyclonal antibody in a sandwich arrangement. Methods: Ferritin was isolated from toucan liver and used as a standard. A rabbit polyclonal anti-toucan antibody was used as the capture antibody and as a detection antibody conjugated to horseradish peroxidase. Linearity of toucan ferritin standards, effect of serum dilution, recovery of added ferritin standards, and intra- and inter-assay variability were determined. Results: Ferritin standards were linear from 0 to 50 ng/ml. The relationship between serum dilution and serum ferritin concentration was also linear. When 10, 20, 30, 40, or 50 ng/ml of purified toucan ferritin were added to diluted serum, the recoveries varied from 69% to 104%. The intra-assay variability for four test serum samples averaged 11% and the inter-assay variability for the same four samples averaged 11%. Conclusions: Although the results from the linearity and recovery studies are promising for assay development when viewed independently, preliminary ferritin concentrations from all toucans studied are much higher than expected. Upon further evaluation including Dot blot assays, Western blot assays, SDS-PAGE, and protein determination of the ferritin stock solution, it was determined that the ferritin stock solution did not contain a pure protein and therefore likely renders the assay invalid. Further testing is needed to confirm these findings.
Keywords: Ferritin; Iron storage disease; Toucans; Enzyme-linked immunosorbent assay; Veterinary Medicine (0778)